Islamic Republic of Afghanistan : 2011 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility-Staff Report; Staff Supplement-A Joint World Bank/IMF Debt Sustainability Analysis; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Islamic Republic of Afghanistan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Afghanistan has made important achievements in recent years. The 2011 Article IV Consultation highlights that authorities have taken steps to lay the foundation for economic stability and growth, despite a very difficult security situation and the challenges associated with building political and economic institutions. Directors agreed that the Extended Credit Facility (ECF)-supported program, accompanied by a technical assistance agenda, provides an appropriate framework for addressing the considerable challenges lying ahead and a basis for continued engagement with the donor community.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet